Two Enfants Terribles in Dutch Exile: The Exilic Posture of Jaroslav Hutka and Ivan Landsmann - Sedláčková, Lucie (Acta Universitatis Carolinae. Philologica, 2021)
This article addresses the topic of authorial posture (as defined by Jérôme Meizoz), in particular the exilic posture. Some exiled authors, listed as examples, or prototypes of that posture, were able to achieve a stable place in the Dutch literary or cultural field. This text shows, however, that some exiled authors or artists were not endowed with the crucial qualities and abilities, and it investigates what kind of qualities and abilities they missed. The Czechs Jaroslav Hutka and Ivan Landsmann spent a part of their lives in exile in the Netherlands, where they also created literary texts. The songwriter, poet and prosaist Hutka and the novelist Landsmann did acquire a firm position in the Czech cultural and literary field without really penetrating the Dutch one. This article examines the extent to which they represented the exilic posture, describes it in more detail, and provides more fitting designations. By doing so, it answers the question why these two authors did not or could not acquire an established position in the Dutch cultural field during their exile period